PENGARUH KEBIASAN BELAJAR DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR: (Survey pada peserta didik kelas XI SMA Muhammadiyah Singaparna Tahun Ajaran 2024 / 2025) - Bayu Tri Pamungkas; Gugum Gumilar; Ati Sadiah (JURNAL ILMIAH NUSANTARA, 2025)
The problem in this study is the low learning outcomes of students. The research method used is the explanatory survey method. The population in this study were grade XI students at SMA Muhammadiyah Singaparna. The sampling technique used saturated so that 74 respondents were obtained. The data collection technique used a closed questionnaire and the data analysis technique used normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, R2 determination coefficient test, t test, and F test. The results of the study showed that 1) There is an influence of learning habits on student learning outcomes with a significance value (0.000 <0.05). 2) There is an influence of learning facilities on student learning outcomes with a significance value (0.005 <0.05). 3) There is an influence of learning habits and learning facilities on student learning outcomes with a significance value (0.000 <0.05).